PERTANGGUNGJAWABAN PEMERINTAH IRAN TERHADAP PEMBAKARAN GEDUNG DIPLOMATIK DAN PERLINDUNGAN HUKUM BAGI PEJABAT BERADASARKAN KONVENSI WINA 1969 - Wildam Apdion Pratama; Wisnu Aryo Dewanto; Suhariwanto Suhariwanto (Perpustakaan Universitas Surabaya, 2018)
This article take a main issue about prohibiton of diplomaitc and protection for state officials doing his duty who related cases for prohibiton about combustion of diplomatic embassy with the incident in Teheran which a indicate to goverment intervention releted with the cases of combustion diplomatic embassy to makes some the necessity of provisons about a protect for diplomatic embassy and also state officials which is set forth on Wina convention 1969 and draft article state responbilty specialty on article 30.